Age-period-cohort analysis of smoking prevalence trends among career military personnel in South Korea - Sunju Jung; Heewon Kang; Sung-il Cho (Tobacco Induced Diseases)
Introduction This study evaluated smoking trends among career military personnel in South Korea. After a tobacco tax increase in 2015, the tobacco control program for career military personnel expanded significantly. This study explores longterm smoking trends among career military personnel through age-period-cohort (APC) analysis within the context of targeted tobacco control policies.